AKIBAT HUKUM PERJANJIAN KERJASAMA KEPEMILIKAN MODAL ANTARA PT. AMBARA PRANATA DENGAN PT. MACCARONI APABILA TERJADI WANPRESTASI - Megarini, Sundari; Westra, I Ketut; Darma Kusuma, A. A. Gde Agung (Kertha Semaya : Journal Ilmu Hukum, 2014)
Economical growth raises many variations of businesses, namely, by entering into cooperation amongst business actors, as not all kinds of businesses they can control. Then through agreement of difference, it can be accommodated and further framed with legal work equally and purposefully as well as to eliminate breach of contract in the agreement made by the parties. The form of agreement between PT. Ambara Pranata and PT. Maccaroni is capital ownership cooperation. There are 16 articles made in this agreement to meet the performance of both parties.
Keywords: Agreement, Cooperation, Capital, Default